PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN RASA PERCAYA DIRI DAN HASIL BELAJAR SENI BUDAYA PADA MATERI PEMBELAJARAN PAMERAN KELAS IX-3 SMP NEGERI 7 MEDAN TAHUN AJARAN 2016/2017 - Jennie Rosinta Adelaide Simanungkalit (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
This study aims to increase self-confidence through the Contextual Teaching and Learning (CTL) learning model. Type of research PTK. The research subjects of Class IX-1 SMP Negeri 7 Medan were 30 people. Based on the results of the research on the learning outcomes test in cycle I, the number of student learning completeness reached 28 students (93.33%) with an average of 78. In the second cycle the number of student learning completeness reached 26 students (86.67%) with an average of 73.83 said not increase then it will proceed to the third cycle. In the learning outcomes test in cycle III, the number of student learning completeness reached 29 students (96.67%) with an average of 79.50. This can be seen from each cycle of an increase.